CircTCF25 serves as a sponge for miR‐206 to support proliferation, migration, and invasion of glioma via the Jak2/p‐Stat3/CypB axis. Issue 6 (5th April 2022) - Yin, Hang; Wang, Hongyu; Wang, Maolin; Yan, Yunji; Dong, Qiang; Li, Qiao; Liu, Yang; Wang, Xiaoqing; Guo, Tianxue; Niu, Liang; Zhang, He; Wang, Bo; et al.
Abstract: Glioma is the most common primary malignant intracranial tumor in humans, and glioblastoma (GBM) has been associated with a more aggressive histology and poorer prognosis. There is growing evidence that circular RNAs (circRNAs) are involved in the progression of various malignancies; however, the role and molecular mechanism of circRNAs in glioma remain elusive. In the present study, we screened for differentially expressed circRNAs in gliomas by using a bioinformatics method. Significant upregulation in glioma tissues was verified by quantitative real‐time polymerase chain reaction (qRT‐PCR), and the prognostic value was evaluated. The potential oncogenic role of circular RNA TCF25 (circTCF25) in glioma was assessed both in vivo and in vitro. Bioinformatics analysis and luciferase reporter assays confirmed the interaction among circTCF25, microRNA‐206 (miR‐206), and its target gene Cyclophilin B (CypB). circTCF25 was predominantly located in the cytoplasm; the combination of mir‐206 and circTCF25 reverses the effects of knockdown of circTCF25 on the proliferation, migration, invasion, and tumorigenesis of glioma cells. Competitive binding between circTCF25 and miR‐206 mainly upregulates target gene CypB expression by preventing its inhibition of the Jak2/p‐stat3 pathway. In addition, knockdown of circTCF25 reduced CypB expression by inhibiting JAK2/p‐stat3, which was rescued by treatment with a miR‐206 inhibitor. In summary, our findings demonstrate that the circTCF25/miR‐206/CypB axis plays a vital role in glioma progression, migration, invasion, and tumorigenesis.